2008
DOI: 10.1186/1471-2199-9-44
|View full text |Cite
|
Sign up to set email alerts
|

A GATA4/WT1 cooperation regulates transcription of genes required for mammalian sex determination and differentiation

Abstract: Background: In mammals, sex determination is genetically controlled. The SRY gene, located on Y chromosome, functions as the dominant genetic switch for testis development. The SRY gene is specifically expressed in a subpopulation of somatic cells (pre-Sertoli cells) of the developing urogenital ridge for a brief period during gonadal differentiation. Despite this tight spatiotemporal expression pattern, the molecular mechanisms that regulate SRY transcription remain poorly understood. Sry expression has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 71 publications
6
107
1
1
Order By: Relevance
“…GATA4 and WT1 initiate the expression of Sry in the male sex-determination pathway. 30) Dmrt1 acts downstream of Sry, 3) leading to the expression of Sox9. The activated Sox9 further stimulates the expression of other key genes, including Fgf9 and PDGS, in testis differentiation and recruits Sertoli cells in the developing testis.…”
Section: Expression and Regulation Of Genes Related To Sex Determinatmentioning
confidence: 99%
“…GATA4 and WT1 initiate the expression of Sry in the male sex-determination pathway. 30) Dmrt1 acts downstream of Sry, 3) leading to the expression of Sox9. The activated Sox9 further stimulates the expression of other key genes, including Fgf9 and PDGS, in testis differentiation and recruits Sertoli cells in the developing testis.…”
Section: Expression and Regulation Of Genes Related To Sex Determinatmentioning
confidence: 99%
“…The authors found that the estrogen receptor 1 (ESR1), Wilms Tumor 1 (WT1), and GATA binding protein 4 (GATA4) had increased expression in MRKH patients [2]. This was a significant finding given that WT1 and GATA4 play significant roles in male sex differentiation via regulation of AMH and that estrogen has been reported to regulate AMH [102,103]. The authors hypothesized that the increased expression of the genes might lead to increased AMH promoter activity during development and subsequent Müllerian duct regression leading to a MRKH phenotype [2].…”
Section: Müllerian Aplasiamentioning
confidence: 59%
“…WT1 and GATA4 regulate sex determination and differentiation via anti-Mullerian hormone (AMH) (23). WT1 and GATA4 are demethylated in patients with MRKHS when compared with healthy volunteers.…”
Section: Mrkhs and Epigenetic Abnormalitiesmentioning
confidence: 99%